Construction of Integrated Islamic School Identity - Majid, Ach Nurholis; In'am, Akhsanul; Haris, Abdul; Romelah, Romelah; Harun, Makmur (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The problem of the identity of educational institutions is a matter of awareness, attitudes, and actions. Institutions with a clear identity also produce clearer educational processes, ecosystem and relations between educational institutions. The problem is that Islamic educational institutions are often seen as monolithic and stigmatized as second-class educational institutions. For this reason, this article focuses on constructing the identity of SDIT Al-Hidayah and SDIT Al-Wathaniyah in Sumenep, Madura. To answer the focus of this article, a qualitative approach was used by choosing the type of case study based on a multi-site design. Data collection was conducted through interviews, observation, and documentation. The data were then analyzed using an interactive analysis model, which included data collection, condensation, data display, and conclusions. Credibility, transferability, dependability, and confirmability tests were conducted to determine the validity of the data. The results of this study indicate that, in general, the construction of the identity of Integrated Islamic Primary Schools in Sumenep consists of three essential elements, namely Islamicity, integration and locality. Islamicity means that the entire identity of the integrated Islamic schools is based on the Islamic values of Ahlussunnah wal Jamaah. The identity of integration refers to the integration of the curriculum, the roles of teachers and parents, the identity of the soul of educators, and the integration of institutions under one foundation. Meanwhile, local identity is an identifying identity taken from local wisdom, such as a Qur'ani-inspired school, a madrasah-nuanced school, and a philanthropic school.